The Significance of Strategic Competence in The Training of Students of Future Teachers of PreDuction Military Education - Rakhmatullaev Umid Karabayevich (Genius Journals, 2023)
The article talks about the importance of strategic competence in teaching students of future teachers of pre-conscription military training. Strategic competence as one of the significant characteristics of students of future teachers of pre-conscription initial training for successful intercultural communicative activity
Keywords: teacher; student; formation